Penerapan Model Pembelajaran ARIAS Berbantuan Video Terhadap Motivasi Dan Pemahaman Konsep Fisika Peserta Didik Kelas VIII MTsN Durian Tarung - Sadraini, Sadraini; aswirna, prima; Roza, Media (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The purposes of this research to know the differences of motivastion and comprehension of physics concepts with the implementation of ARIAS learning models aided video, which is better than conventional learning models in class VIII in MTsN Durian Tarung. This research uses quasi experiment with randomized control group only design. The population of thisÂ  research is the student of class VIII at MTsN Durian Tarung2016/2017which consist of eight class. The sample of the reseacrh use cluster random sampling technique, VIII8 as experiment group and VIII6 as control group. The instrumen of this research is quationer motivation and tes of physic concept of learners in the form of essay. The result showed that the average of experimental class motivation was 115,61 and control class was 95,39. Meanwhile, the average result of understanding physics concepts of experimental class students 80.03 and control class 75,11.Data analyzed uses t-test independent with SPSS 16.0. version. The research has shown the application of ARIAS learning models aides video provides better motivation with t-test, t hitung >t table = 6.412> 1.667and physics conceptswith t-test t hitung >t table = 2.538> 1.667than conventional learning models in class VIII MTsN Durian Tarung.